PEMAHAMAN PENDIDIK ATAS KURIKULUM DAN IMPILIKASINYA TERHADAP KUALITAS PEMBELAJARAN DI DAARUL QUR’AN INTERNATIONAL PRIMARYSCHOOL KOTA TANGERANG BANTEN - Nuruddiniah, Diah; Sastradihardja, EE. Junaedi; Shunhaji, Ahmad (STKIP Pesisir Selatan, 2025)
Education is the foundation of civilization that shapes quality individuals, requiring curriculum adaptation and a deep understanding from educators as key prerequisites. Educators' understanding of the curriculum is a vital key that influences planning, implementation, and evaluation of learning, and has high urgency given the dynamics of curriculum change and the demands for sustainable education quality. This study aims to identify the level of educators' understanding, the factors influencing it, as well as the direct and indirect impacts on the learning process and outcomes. Using a qualitative approach with a case study at Daarul Qur'an International Primary School, this research involves educators as participants. Data were collected through interviews, observations, and document analysis, then analyzed thematically. The results show variations in educators' understanding of the curriculum, influenced by training, pedagogical competencies, positive perceptions of curriculum changes, school principal support, adaptation challenges, participation in professional learning communities, resource availability, and digital literacy. Curriculum understanding positively correlates with teaching performance. In conclusion, educators' deep understanding of the curriculum has a significant impact on the quality of the learning process and outcomes.